Development of scientific and methodological basis of information protection: development of physical model of artificial molecular memory based on phenol derivatives - Ключко, Олена Михайлівна; Білецький, Анатолій Якович; Шутко, Владимир Николаевич; Колганова, Олена Олегівна (Ukrainian Information Security Research Journal, 2020)
Exploration and engineering work aimed at creating of elements and devices of nano-electronic memory (physical molecular memory) are extremely relevant nowadays. Intensive works in this direction is carried out, including ones by finding of new promising chemical compounds - candidates for the functions of physical molecular memory elements, as well as by creating new physical models of relevant devices and their nano-elements. The aim of this work was to propose a new type of chemical compounds of phenol derivatives set that could potentially be used to perform the functions of molecular memory for nano-electronic devices, as well as to develop a physical model of such memory and to explain its mechanism. For the described physical model of artificial molecular memory, it is proposed to use molecules - phenol derivatives with substituents - polyamine chains, linear or branched, of different length and complexity. A physical model of molecular storage devices with artificial memory properties has been developed. Technical result that could be obtained by such work performing is that the proposed method allows to modify and to create new memory elements of artificial origin, as well as to test their functioning by the registration of electric currents through the formed sample. The recorded currents were asymmetric, demonstrating the properties of memory of the sample. The proposed invention opens new opportunities for the information protection in such information systems.